Red Pomegranate Extracts on Catalase Levels in Huvecs Culture Which are Exposed Preeclampsia Plasma - Januarsih Januarsih (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2018)
In a normal pregnancy, there is an increase in the production of free radicals, compared to on not pregnant and when the preeclampsia occurs the production is even more. This situation controlled with anti-oxidants. In general, antioxidants divided into two groups, namely: enzymatic antioxidants / primary antioxidants / antioxidant deterrents and nonenzymatic antioxidants consist of SOD, GPx and CAT. The purpose of this study is to determine the effect of giving Pomegranate Fruit extract to CAT levels in HUVECs who exposed to plasma preeclampsia. This study used a laboratory exploration method with samples: 1 negative control group (HUVECs culture exposed to normal 2% plasma pregnancy). One positive control group (HUVECs culture exposed to 2% preeclamptic plasma) and three treatment groups (HUVECs culture exposed to plasma 2% preeclampsia was given red pomegranate extract at different doses of 14 ppm, 28 ppm, 56 ppm, followed by calculating the amount of CAT which was a marker of intracellular antioxidants. Using the assumption of normality and homogeneity of variance tests that was using the Levene test as a prerequisite for parametric statistical testing, (2) One Way ANOVA Test (F Test), and (3) Pearson correlation test. The result is Red Pomegranate extract can prevent a decrease in CAT levels at a dose of 56 ppm. In conclusion, the Pomegranate Fruit extract can increase CAT levels